2018
DOI: 10.1017/cjn.2017.292
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cerebral Perfusion Pressure on Acute Respiratory Distress Syndrome

Abstract: We did not observe an association between increased CPP and ARDS. Patients with ARDS had higher ΔP and lower lung compliance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…ARDS is characterized by diffuse lung parenchymal inflammation, noncardiogenic pulmonary edema due to increased alveolar-capillary vascular permeability , leading to impaired gas exchange resulting in hypoxemia and abnormal lung physiology [ 4 ]. The mechanism of ARDS associated with TBI is related to catecholamine surge, and systemic inflammation response causing abnormally elevated pulmonary hydrostatic pressure and vascular permeability, pulmonary edema coupled with systemic arterial hypertension to maintain the cerebral perfusion pressure (CPP) in the presence of intracranial pressure (ICP) crisis [ 5 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…ARDS is characterized by diffuse lung parenchymal inflammation, noncardiogenic pulmonary edema due to increased alveolar-capillary vascular permeability , leading to impaired gas exchange resulting in hypoxemia and abnormal lung physiology [ 4 ]. The mechanism of ARDS associated with TBI is related to catecholamine surge, and systemic inflammation response causing abnormally elevated pulmonary hydrostatic pressure and vascular permeability, pulmonary edema coupled with systemic arterial hypertension to maintain the cerebral perfusion pressure (CPP) in the presence of intracranial pressure (ICP) crisis [ 5 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, a recent multicenter randomized trial reported no increase in adverse effects using a protocol aimed at optimizing brain tissue oxygen tension (P bt O 2 ), even though augmenting CPP was one of numerous interventions that could be used to raise P bt O 2 [31]. Similarly, a single-center cohort study found no association between higher CPP and acute respiratory distress syndrome [32]. Regardless, any algorithm that is used in future clinical trials to adjust the CPP target must incorporate careful cardiopulmonary monitoring and safeguards to minimize complications.…”
Section: Gos-e 1-3 Gos-e 4-8 P Valuementioning
confidence: 93%
“…Previous studies have shown that ARDS was a common pulmonary complication in TBI patients with the incidence ranging from 1% to 60% [ 2 , 3 ]. ARDS also has been confirmed as a risk factor for poor prognosis including higher mortality, poorer neurological outcome and longer length of hospital stay in some studies [ 4 , 5 , 6 , 7 ]. Studies have explored risk factors for ARDS in TBI patients including younger age, male sex, admission tachycardia, underlying respiratory and vascular diseases, pneumonia, head AIS, early crystalloids, early platelet transfusion and intracranial hypertension [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%